Inovasi Solar Dryer Aktif untuk Meningkatkan Kualitas dan Efisiensi Pengeringan Biji Kakao Pascapanen - Nely Ana Mufarida; Machmud Effendy; Sofia Ariyani (Universitas Muhammadiyah Metro, 2026)
Drying is a crucial stage in post-harvest handling of cocoa beans because it significantly determines the final quality, storage stability, and market value of the product. Traditional drying methods, still widely used by farmers, often face challenges such as weather dependence, long drying times, and the risk of contamination. This study aimed to evaluate the performance of an active solar dryer as a more efficient and hygienic alternative technology. A prototype was designed using solar collectors and a solar panel-powered ventilation system to maintain a steady flow of hot air throughout the drying process. The results showed that the active solar dryer was able to maintain a drying temperature of 45–60°C, reducing the moisture content of cocoa beans from approximately 58% to 7% in 48–72 hours. In contrast, traditional methods require 120–144 hours to achieve the same moisture content. The physical quality of cocoa beans produced by the active solar dryer was superior, with a more uniform color, an even dry texture, and no signs of case hardening. Furthermore, the fermentation aroma was stronger and the level of microbial contamination was lower than that of traditional drying. Overall, the active solar dryer technology has been shown to improve drying efficiency and cocoa bean quality, thus offering potential for widespread adoption at the farmer level.